Burn injury prevention in low- and middle- income countries: scoping systematic review. Issue 1 (29th October 2021) - Price, Kate; Lee, Kwang Chear; Woolley, Katherine E; Falk, Henry; Peck, Michael; Lilford, Richard; Moiemen, Naiem
Abstract: Background: Burn injuries are a leading cause of morbidity and disability, with the burden of disease being disproportionately higher in low- and middle-income countries (LMIC). Burn prevention programmes have led to significant reductions in the incidence of burns in high-income countries. However, a previous systematic review published in 2015 highlighted that implementation and evaluation of similar programmes has been limited in LMIC. The objective of this scoping review and narrative synthesis was to summarise and understand the initiatives that have been carried out to reduce burn injuries in LMIC and their effectiveness. Methods: We aimed to identify publications that described studies of effectiveness of burn prevention interventions applied to any population within a LMIC and measured burn incidence or burns-related outcomes. Suitable publications were identified from three sources. Firstly, data was extracted from manuscripts identified in the systematic review published by Rybarczyk et al . We then performed a search for manuscripts on burn prevention interventions published between January 2015 and September 2020. Finally, we extracted data from two systematic reviews where burn evidence was not the primary outcome, which were identified by senior authors. A quality assessment and narrative synthesis of included manuscripts were performed. Results: In total, 24 manuscripts were identified and categorized according to intervention type. The majority of manuscripts ( n  = 16) described education-based interventions. Four manuscripts focused on environmental modification interventions and four adopted a mixed-methods approach. All of the education-based initiatives demonstrated improvements in knowledge relating to burn safety or first aid, however few measured the impact of their intervention on burn incidence. Four manuscripts described population-based educational interventions and noted reductions in burn incidence. Only one of the four manuscripts describing environmental modification interventions reported burns as a primary outcome measure, noting a reduction in burn incidence. All mixed-method interventions demonstrated some positive improvements in either burn incidence or burns-related safety practices. Conclusion: There is a lack of published literature describing large-scale burn prevention programmes in LMIC that can demonstrate sustained reductions in burn incidence. Population-level, collaborative projects are necessary to drive forward burn prevention through specific environmental or legislative changes and supplementary educational programmes.